Effects of Protein-Energy Wasting (PEW) and hyperphosphatemia on the prognosis in Japanese maintenance hemodialysis patients: A five-year follow-up observational study. (April 2020) - Inoue, Arisa; Ishikawa, Eiji; Shirai, Yumiko; Murata, Tomohiro; Miki, Chikao; Hamada, Yasuhiro
Summary: Background & aims: In dialysis patients, malnutrition is a poor prognostic factor. In patients with chronic kidney disease (CKD), malnutrition is qualitatively different from general malnutrition, which is defined as "Protein-Energy Wasting (PEW)." Dietary therapy for the enhancement of PEW requires the aggressive intake of protein. Conversely, as protein intake and phosphorus intake correlate positively, increasing the protein intake increases the phosphorus intake, which is a poor prognostic factor in dialysis patients. One of the treatments for hyperphosphatemia in dialysis patients is the intake restriction of phosphorus by dietary counseling. However, protein uptake to maintain and augment the nutritional status and the protein intake restriction to correct hyperphosphatemia are contradictory treatments. Hence, this study aims to investigate the effects of PEW and hyperphosphatemia on the prognosis in hemodialysis patients. Methods: We enrolled 60 outpatients who underwent maintenance hemodialysis for 6 months (May–November 2012) at Iga City General Hospital (Mie, Japan). In November 2012, we assessed the presence or absence of PEW and hyperphosphatemia in patients and evaluated the survival rate over the next 5 years. Results: Overall, 10 patients (17%) were diagnosed as PEW. While 17 patients (28%) exhibited average phosphorus level >6.0 mg/dL (hyperphosphatemia). The 5-year survival rate was 30% in the PEW group, 66% in the non-PEW group, 57% in the hyperphosphatemia group, and 61% in the non-hyperphosphatemia group. A statistically significant difference existed between the PEW and non-PEW groups ( P = 0.021). However, we observed no significant difference between the hyperphosphatemia and non-hyperphosphatemia groups. Conclusions: This study suggests that PEW affects the prognosis more than hyperphosphatemia in maintenance hemodialysis patients. The normalization of the serum phosphorus level by the protein intake restriction could prevent secondary hyperparathyroidism and vascular calcification. Conversely, restricting the protein intake poses a risk of malnutrition. In fact, early death occurred in patients with PEW in this study. Perhaps, patients with PEW should prioritize improving their nutritional status rather than controlling the serum phosphorus level. Highlights: To maintain good nutritional status in dialysis patients is important for survival. PEW affects prognosis more than hyperphosphatemia in hemodialysis patients. Hemodialysis patients should prioritize improvement in PEW.